KARAKTERISASI BAKTERI TANAH PERTANIAN ORGANIK DAN TANAH PERTANIAN ANORGANIK DAN UJI ANTAGONIS TERHADAP JAMUR AKAR PUTIH (Rigidoporus microporus) - Widya Lestari; Kamsia Dorliana Sitanggang (UNIVERSITAS LABUHANBATU, 2020)
Research on the Characterization and Antagonist Test of Organic Soil Bacteria and Inorganic Farm Soils Against White Root Fungi (Rigidoporus microporus), was studied at the USU FMIPA Microbiology Laboratory, Medan, in May 2018. The method used was the characterization of agricultural soil bacteria with scatter plates and Yeast media. Extract 1%, obtained 3 soil bacterial isolates namely Sp01, Sp02 and Sp03 and 3 isolates from the inorganic agricultural soils Spa1, Spa2, and Spa3 which were characterized by shape, color, elevation edge and edge of the colony. Sp02 and Sp03 bacteria have greater ability to inhibit the growth of Rigidoporus microporus than Sp01 with inhibition zones of 2.5 and 3.5 mm. Sp a1 bacterium has the highest inhibitory ability of 30 mm against Rigidoporus microporus compared to Spa2 and Spa3. Keywords: Bacteria, Rigidoporus microporus, Faarm soils